Pragmatics and its interfaces - Ilie, Cornelia; Norrick, Neal R. (Pragmatics & beyond., 2018)
This volume offers state-of-the-art overviews of the cross-disciplinary role and impact of Pragmatics in relation to several areas of study that it interfaces with. Pragmatics has contributed significant insights to a range of disciplines, just as these disciplines have contributed to it. Borrowing and cross-pollination between disciplines is natural, as well as necessary, but at times it seems important to take a pause and reflect on and problematize the role of pragmatics at these interfaces. In an age when disciplinary boundaries are being blurred, we need to investigate the relationship and interplay between pragmatics and related or complementary fields of enquiry with the goal of broadening and deepening our understanding of the contributions and boundaries of pragmatics as such. Here in twelve original contributions, internationally recognized authorities explore the current state and future trends in Pragmatics vis-à-vis adjacent disciplines.